Monuments & Memory: Christian Cult Buildings and Constructions of the Past - Verhoeven, Mariëtte; Bosman, Lex; van Asperen, Hanneke (Brepols, 2016)
This volume honours Sible de Blaauw on the occasion of his retirement from Radboud University. It is above all a tribute to an influential and respected voice in the field of early Christian art and architecture. Thirty-one authors have sought to provide their own unique answer to the question of how Christian cult buildings have played a role in cultural memory in different periods and in various geographical and cultural contexts. From its very onset, this publication was envisioned as a parallel to De Blaauw’s own research interests: Rome and its monuments, early Christianity, Christian religious heritage, liturgy and architecture, continuity of tradition, and memory. The contributions have been arranged according to three sections: <span class=